2005
DOI: 10.1590/s0004-27302005000500010
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma diferenciado de tireóide: avaliação inicial e acompanhamento

Abstract: RESUMOO câncer de tireóide é responsável por cerca de 1% dos novos casos de doença maligna diagnosticados. A maioria destes tumores são carcinomas papilares e foliculares, também denominados de carcinomas diferenciados de tireóide (CDT). Estes carcinomas têm uma taxa de cura de aproximadamente 80%, enquanto 20% apresentarão recorrência local e 5 a 10% desenvolverão metástases à distância. Porém, alguns pacientes apresentam uma doença mais agressiva. A identificação de tais pacientes tem grande impacto no manej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
1
7
0
8
Order By: Relevance
“…20 Regarding thyroid gland tumors, our results indicated that surgery was the most preva- seem to determine a more favorable prognosis for patients with thyroid cancer. 37 In analyzing the tumor stage, a high proportion of tumors classified as T3 and T4 was observed.…”
mentioning
confidence: 67%
“…20 Regarding thyroid gland tumors, our results indicated that surgery was the most preva- seem to determine a more favorable prognosis for patients with thyroid cancer. 37 In analyzing the tumor stage, a high proportion of tumors classified as T3 and T4 was observed.…”
mentioning
confidence: 67%
“…Arq Bras Endocrinol Metab. 2010;54(4): clinical case report 1 T hyroid cancer is the most frequently occurring endocrinal tumor, although it represents less than 1% of all malignant tumors diagnosed worldwide (1). Patient management usually consists of thyroidectomy, either entire or nearly so, followed by radioiodine therapy in the case of differentiated thyroid cancer (papillary and follicular tumors).…”
Section: Sumáriomentioning
confidence: 99%
“…Medullary thyroid cancers that are parafollicular thyroid C cells in origin have been observed in about 5% of all thyroid cancers [1]. Follicular thyroid cell-derived tumors include papillary thyroid cancer (PTC), follicular thyroid cancer, and anaplastic thyroid cancer [5,6,7,8,9]. PTC and follicular thyroid cancer are collectively classified as well-differentiated thyroid cancers and account for around 95% of thyroid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations or loss of heterozygosity of the genes SDHA, SDHB, SDHC, and SDHD have been described in paragangliomas, pheochromocytomas [19,20,21,22], renal cell carcinoma [19,23,24], gastrointestinal carcinoma [19], familial pheochromocytoma and paraganglioma [14,24,25,26,27], Cowden's syndrome [22,23], medullar [1,19] and papillary thyroid carcinoma [14,19,24], and more recently pituitary adenomas [28,29,30]. …”
Section: Introductionmentioning
confidence: 99%